2021
DOI: 10.3390/plants10122562
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Water Yam (Dioscorea alata L.) Accessions from Côte d’Ivoire Based on SNP Markers and Agronomic Traits

Abstract: Dioscorea alata (L.), also referred to as water, winged, or greater yam, is one of the most economically important staple food crops in tropical and subtropical areas. In Côte d’Ivoire, it represents, along with other yam species, the largest food crop and significantly contributes to food security. However, studies focusing on better understanding the structure and extent of genetic diversity among D. alata accessions, using molecular and phenotypic traits, are limited. This study was, therefore, conducted to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Results of the AMOVA revealed high genetic variation among the three clusters and lower genetic variation among landraces within clusters. Similarly, Bakayoko et al. (2021) reported low molecular variability within groups and high between groups of D. alata accessions from Côte d’Ivoire using SNP markers.…”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…Results of the AMOVA revealed high genetic variation among the three clusters and lower genetic variation among landraces within clusters. Similarly, Bakayoko et al. (2021) reported low molecular variability within groups and high between groups of D. alata accessions from Côte d’Ivoire using SNP markers.…”
Section: Discussionmentioning
confidence: 91%
“…Results of the AMOVA revealed high genetic variation among the three clusters and lower genetic variation among landraces within clusters. Similarly, Bakayoko et al (2021) reported low molecular variability within groups and high between groups of D. alata accessions from Cote d'Ivoire using SNP markers. High levels of genetic variation among clusters of yam landraces in Nigeria indicated a lack of gene flow, possibly due to low seed-yam (mini or small whole tubers or portion of tubers used for propagation) exchange among farmers in geographically distant areas.…”
Section: Figurementioning
confidence: 93%
See 3 more Smart Citations